The Effectiveness of Two -Way Communication; Listen and Respond To Children Aged 4 Years - Siti Isnaini; Dhiya Susanti; Mufaro’ah (Penerbit Hellow Pustaka, 2024)
Two-way communication, involving the processes of listening and responding, plays a crucial role in social interaction and education, particularly for early childhood. At the age of 4, children's communication abilities begin to develop more actively and complexly, affecting their language, emotional, and cognitive development. Effective communication from parents and educators, especially through active listening and appropriate responses, helps children develop language skills and strong emotional attachment. By giving full attention when children speak and responding empathetically, adults can build the child's confidence and motivation to learn. Furthermore, good two-way communication contributes to the child's social development, enhancing their ability to interact with others and fostering critical thinking. Optimal communication strategies, such as active listening, open-ended questions, and positive reinforcement, have proven effective in stimulating the social and cognitive development of young children.